Homonimija in polisemija v dvojezičnih slovarjih za slovenske priseljence v ZDA v začetku 20. stoletja - Vrbinc, Alenka (Slovenski jezik, 2024)
Regrettably, scholarly attention has been limited concerning dictionaries designed for immigrants, what could be called immigrant dictionaries. These books, which aim to address the immediate requirements of new immigrants, are part of the broader sphere of learner lexicography. This article scrutinizes four such immigrant dictionaries, Slo- 178Slovenski jezik – Slovene Linguistic Studies 16 (2024)venian–English and English–Slovenian works published in the early twentieth century during the peak of Slovenian immigration to the United States (Kubelka 1904, Kubelka 1912, Košutnik 1912, and Kern 1919). The analysis focuses on the presentation of information, examining the dictionaries’ treatments of homonymy, polysemy, conver-sion, and parenthetical information. The article discusses implications of adopting a macrostructure-oriented approach or a microstructure-oriented one, in terms of which best facilitates the comprehension of immigrant users. The research findings highlight the significance of lexicographic presentation in the microstructure of immigrant dic-tionaries. The recommendation is to prioritize the presentation of meaning over other elements typically covered in dictionaries, when a dictionary is intended for immigrants.
Keywords: conversion; homonimija; homonymy; immigrant dictionaries; konverzija; parenthetical information; polisemija; polysemy; slovarji za priseljence; usmerjevalne besede v oklepaju